GENDER DIFFERENCES ON COMMUNICATION IN TRADITIONAL MARKET OF MEDAN - Sipahutar, Afrida Fitriyani (English Language Teaching Prima Journal (ELT), 2023)
This paper deals with gender differences on communication. The aim of this paper is to analyse how female buyer and male seller communicate and different characteristics of female buyer and male seller in the market especially in process of buying and selling. The data of this study is the language differences between male seller and female buyer in traditional market of Medan, while the source of data of this study is the utterences of male seller and female buyer. In this study, the writer uses qualitative method because the data will be delivered by giving explanation in the form of words and sentences. The instrument of data collection are recorder and interview. The result of analysis shows that there are many differences of communication between female buyer and seller in the market. Female buyer mostly used polite form in conversation with male seller. Male seller tend to use the language directly and indirectly. He used direct and indirect communication based on the context of communication.